The Influence of Using Muslim Pro Application as a Learning Medium on Students' Understanding of Tajweed Laws at MTs 10 Agam - Irfan Asyari; Feby Hidayati (JEICI - Journal of Education and Islamic Contemporary Issue, 2025)
Using the Muslim Pro application in learning Tajweed science material will make it easier for students to learn, not get bored in memorizing the Qur'an and can prepare for life in the 5.0 era. The type of research used is a quantitative research method using a quasi-experimental approach, with a Nonequivalent Control Group Quasi design. Researchers provide treatment and examine changes or differences from the treatment that has been given. Quasi-experimental research has the aim of finding out variables that will involve between the control class and the experimental class. Decision making significant value <0.05 indicates a significant difference between the initial variable and the final variable. The sig value has a value of 0.000, this indicates that there is a significant influence on the difference in treatment given to each variable. So it can be concluded that "there is an influence in the use of the Muslim Pro application as a learning medium for Tajweed law for class VII MTsn 10 Agam in the 2022/2023 academic year".